Performing normative power : analysing speech acts in the European Parliament debate on the murder of Jamal Khashoggi - Heikkinen, Anna-Sofia (2024)
In this master’s thesis I examined what kind of values were emphasised in the European Union’s (EU) response on the murder of Saudi journalist and dissident Jamal Khashoggi. My aim was to analyse the European Parliament (EP) debate on the murder, and to find out the emerging values, as well as the issues raised in the debate regarding normativity and these values. Additionally, I examined if it can be understood that the EU had a strong normative and coherent response to the murder case.